TNC Strategies: Mergers and Acquisitions - Vovk, Svitlana (ТNEU, 2013)
The paper presents the essence, the prerequisites of mergers and acquisitions; it singles out modern trends of mergers and acquisitions, namely the development of the social component of enterprise integration; also the operations are analyzed in merges and acquisitions throughout the whole world and in Ukraine, in particular.
Keywords: Merges and acquisitions; integration